Effects of hardness and salinity on hatch and survival of nile tilapia (Oreochromis niloticus Linnaeus) eggs under hatcherry conditions. - Prasad, Bhagwat; Bart, Amrit N.; Yakupitiyage, Amararatne; Yang, Yi; Joint Japan; World Bank Graduate Scholarship Program; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2004)
Nile tilapia (Oreochromis niloticus) is the most dominant cultured species of the Tilapiine group. Despite the increasing importance of Nile tilapia in aquaculture and increasing demand of their quality seed from the hatcheries, hatch and survival of their eggs to swim-up fry highly variable (12% to 90%). Some studies on the effects of hardness and salinity of hatchery water on egg and larval survival have indicated the imp01iance of these two factors on the incubation success. But, the studies on the role of hardness and salinity of the hatchery water on the hatching and larval survival are lacking. The effects of hardness and salinity on the artificial incubation of Nile tilapia (Chitralada strain) eggs were examined through several experiments. Increasing hardness level to 500-4200 mg/L and 150-1200 mg/L CaC03 in two separate experiments resulted in higher percent survival (51.7% and 26.4%) from eggs to swim-up fry than those (30.3% and 6.1 %) obtained in their respective controls with hardness levels of 50 mg/L. No significant difference (P>0.05) among the percent survival was observed in the treatments with hardness levels of 500-4,200 mg/L and 150-1,200 mg/L respectively, in two experiments. In another experiment where the salinities were prepared by diluting seawater, 4%o resulted in significantly higher {P<0.05) egg to swim-up fry survival (25.7%) than those (0.0-19.1 %) obtained at the other treatments with 0, 2, 6, 8, 12, 16 and 32%0 salinities. In the other experiment where the effects of salinities (4, 8 and 12%0) prepared using commercial grade raw sea salt (CS), iodized table salt with 99.9% NaCl {TS) and seawater (SW) were compared, 4%o of seawater salinity had again the highest survival rate from eggs to swim-up fry (37.4%) when compared to the control (23.35%), 12%0 SW salinity (27.9%) and 4-12%0 TS salinities (0.0-0.4%). The CS salinities of 4 and 8%0 resulted in similar survival rates (33.0 and 35.1 %) as 4%o seawater. In a laboratory experiment, 4 and 8%0 salinities with both analytical grade NaCl (LS) and TS had no survival where as the same salinities prepared by using mixtures of commercial grade calcium chloride and TS (25:75 and 50:50 by weight) resulted nearly 100% survival of Nile tilapia yolksac larvae when exposed for 96 hours (up to swim-up stage). Significant interaction (P<0.01) of salinity and hardness on survival rates of eggs up to swim-up fry was also observed 3x3 factorial experiment (2, 5 and 9%o salinities and 50, 500 and 1000 mg/L hardness). In general, the survival rates decreased with increase in salinity and increased with increase in hardness. Salinity of 2%o or above from NaCl (Prung Thip iodized table salt, 99.9% NaCl) seemed to be associated with low survival of Nile tilapia eggs and fry, but the survival increased by increasing calcium hardness. The treatments with 2%o salinity and hardness of 500 and 1,000 mg/L, and 5%o salinity and hardness of 500 and 1,000 mg/L resulted in higher survival rates (30.5-36.4%) from eggs to swim-up fry than those resulted in rest of the treatments (0.9-22.4%). These series of experiments indicated that the egg hatch could be improved by 11.5-13.4% and larval survival by 10.6-12.3% by increasing salinity of the hatchery water to 4%o (seawater source). Similarly, increase in calcium hardness could increase hatch rate by 22.4% and larval survival by 20.1-21.4%. Moreover, maintenance of hardness at 500 mg/L and salinity of 2%o could significantly add to the larval survival by 28.5%. These findings need to be further verified at commercial scale and then could be extended to the private hatcheries if found promising. The combination of 2%o salinity and 500 mg/L of hardness may be compared with 4%o seawater salinity and 4 and 8%0 CS salinities to examine their comparative effectiveness in further studies.
Thesis (M.Sc.) - Asian Institute of Technology, 2004
A thesis proposal for the partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Keywords: Nile tilapia -- Eggs; Fishes -- Effect of water quality on